Utilization of Programmable Logic Controller (PLC) with System Control Lights On Large Buildings - Fakhrudin, Muhammad Naufal; Siswojo, Bambang; R, Radmahwati (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
Enhancement need for energy electricity in buildings or large buildings​​ will increase waste energy and improve the expenditure of funds. For That need given solution How method saves electricity with cheap and efficient equipment.​ The PLC ( Programmable Logic Controller ) program is A tool operating electronics​ digitally for​ replace Suite a row of relays in a conventional process control system. To carry out its function then the PLC has sensor elements, controllers, and output devices so that capable do task control sequential, control sophisticated, and control supervision. Research results This shows that the application of PLC in buildings or big buildings​ will increase high efficiency​ by utilizing: a) elements of the system control light involving appropriate sensors, controllers (servers), and actuators; b) put sensor devices with appropriate; c) count wide room with lighting appropriate; and d) combine usage halogen lamp as replacement ray sun and TL lamps as lighting normal.